El campesino andino y la globalización a fines de siglo (una mirada sobre el caso ecuatoriano) - Martínez, Luciano (European Review of Latin American and Caribbean Studies, 2004)
The Andean peasant and globalization at the end of the century (a look at the Ecuadorian case)This article explores the current situation of the small landed peasantry in the Ecuadorian Andes, confronted by important changes in the agrarian system, in social relations and in links with the global market. The effects of this situation are: an increase in small farms (which is a progressive loss of land resources), a crisis within the supportive relationships in the community, and a rise in international migration, which is a new process of integration as cheap labour in the global market. The politics of adjustment and the dolarization of the economy have made peasant production less competitive, thus tending to cause proletarianization of labour in the national as well as the international market. From this context, the effects of international migration trends on the social fabric of a peasant organization from the southern Ecuadorian Andes are analyzed.Resumen:Este artículo aborda la situación actual del campesinado minifundista andino del Ecuador, quien enfrenta importantes cambios en la estructura agraria, en las relaciones sociales y en la vinculación con el mercado global. Esta situación se manifiesta a través de: el incremento del minifundio (que implica la pérdida progresiva del recurso de la tierra), la crisis de las relaciones solidarias en las comunidades, y un aumento de la migración internacional – un nuevo proceso de integración como mano de obra barata en el mercado mundial. Con las políticas de ajuste y la dolarización de la economía, la producción campesina se ha convertido poco competitiva, lo que a su vez tiende a proletarizar la mano de obra tanto en el mercado nacional como en el internacional. Desde este contexto, se analizan los efectos de la migración internacional en el tejido social de una organización campesina en el sur de la sierra ecuatoriana.